2017
DOI: 10.1155/2017/8310979
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes of Phenylethyl Resorcinol as Vesicular Delivery System for Skin Lightening Applications

Abstract: Ethosome formulations containing phenylethyl resorcinol (PR) were developed. The formulation was produced from 0.5% w/v PR, 0.5% w/v cholesterol from lanolin, 3% w/v L-α-phosphatidylcholine from soybean, 30% v/v absolute ethanol, and water up to 100% v/v. It was characterized by a vesicular size of 389 nm, low polydispersity index of 0.266, zeta potential of −34.19 ± 0.44 mV, high PR entrapment efficiency of 71%, and good stability on storage at 4 and 30°C at 75% RH for 4 months. In vitro studies using pig ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…On the same line, hybrid poly (lactic-co-glycolic acid) (PLGA) microspheres have been proposed to improve the encapsulation and control the release of amphiphilic compounds such as phenylethyl resorcinol, leading to 40% enhancement of tyrosinase inhibition in mouse melanoma cells [233]. Ethosomes formulations as well as nanostructured lipid carriers (NLCs) with high encapsulation efficiency and stability have also been developed for the delivery of phenylethyl resorcinol into the skin, exhibiting higher tyrosinase inhibition compared to other formulations in B16 melanoma cells [234,235]. Increased loading and chemical stability was achieved also by the use of smartPearls combined with the UV abosorber Tinosorb S [236].…”
Section: New Trends In the Search For Tyrosinase Inhibitorsmentioning
confidence: 99%
“…On the same line, hybrid poly (lactic-co-glycolic acid) (PLGA) microspheres have been proposed to improve the encapsulation and control the release of amphiphilic compounds such as phenylethyl resorcinol, leading to 40% enhancement of tyrosinase inhibition in mouse melanoma cells [233]. Ethosomes formulations as well as nanostructured lipid carriers (NLCs) with high encapsulation efficiency and stability have also been developed for the delivery of phenylethyl resorcinol into the skin, exhibiting higher tyrosinase inhibition compared to other formulations in B16 melanoma cells [234,235]. Increased loading and chemical stability was achieved also by the use of smartPearls combined with the UV abosorber Tinosorb S [236].…”
Section: New Trends In the Search For Tyrosinase Inhibitorsmentioning
confidence: 99%
“…In case of transfersomes, the PR was encapsulated at lipid bilayer of the vesicles. In contrast, ethosomes and invasomes which composed of ethanol in the formulation, the PR could be distributed throughout the vesicle [15][16][17]. The encapsulation of PR within the vesicles helps to protect the PR from the degradation by natural light, resulting in the higher stability for long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ethosomes, transfersomes and invasomes were selected to study on improving stability of PR. All vesicles were prepared accounting to the method of our previous reports [15][16][17]. The main composition of all vesicles composed of 3 % w/v SPC: 0.5 % w/v CHOL: 0.5 % w/v PR: up to 100 % v/v water phase.…”
Section: Preparation Of Vesicular Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, PR is safe to use as skin lightening agent since it is non-toxic. There were no adverse effects such as oedema, erythema and eschar in rabbits after 72 h, when 0.5% PR solution was applied in a shortterm exposure [9]. The clinical study on human subjects revealed that 0.5% of PR was more effective than 1% Kojic acid in skin lightening [10].…”
Section: Introductionmentioning
confidence: 86%